Geo-Information Techniques for Analysis of Foot and Mouth Disease in Cattle Maeon District, Chiang Mai Province - Onmueang, Suchada; Charoenpanyanet, Arisara (Journal of Mahanakorn Veterinary Medicine, 2018)
Geo-Information techniques for analysis of Foot and Mouth Disease in cattle in Maeon district, Chiang Mai province has objectives of study: 1) to analyze distribution pattern of foot and mouth disease in cattle with spatial statistics and 2) to analyze relationship of agents influencing foot and mouth disease in cattle. Geo-Information techniques in animal epidemiology and statistical methods were used in this study. Coordinates of cattle farms from GPS were used to analyze point density. This is to derive distribution pattern of foot and mouth disease. Agents are temperature, humidity, and distance from the road. They were extracted from Landsat 8 and find the correlation between distribution of foot and mouth disease with Pearson’s correlation coefficient. The results found that there is significant (P <0.05) correlation between distribution of foot and mouth disease and agents. Humidity is a strongest correlation (r = 0.972, P = 0.000) followed by temperature r = -0.850, P = 0.000) and distance from road (r = -0.486, P = 0.026), respectively.